PENGARUH PENGEMBANGAN KARIR, MOTIVASI DAN KOMPETENSI TERHADAP KINERJA PEGAWAI DI SEKRETARIAT DAERAH KABUPATEN ENREKANG - Azizah Waty; Syamsu Alam; Laode Amijaya Kamaluddin (Lembaga Penelitian, Publikasi dan Pengabdian Masyarakat ITB Nobel Indonesia, 2022)
This study aims to determine and analyze the influence of career development, work motivation and competence on employee performance at the Regional Secretariat of Enrekang Regency. This research approach uses survey research conducted at the Regional Secretariat of Enrekang Regency in January 2022. The data used in this study are primary data collected through a direct questionnaire survey and using a sample of 75 employees who work at the Enrekang Regency Regional Secretariat. Data analysis used multiple linear regression analysis to test hypotheses 1, 2, and 3. The results of the study using multiple linear regression analysis showed that all variables had a positive and significant effect on employee performance, namely career development, work motivation and competence. The variables of career development, work motivation and competence have a simultaneous effect on employee performance. Keywords: Career development, work motivation, competence, and employee performance